Sefer Yosippon: Reevaluations - Bowman, Steven (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2019)
Author brings here some thoughts for discussion about Sefer Yosippon, that seminal history of Second Temple Jews whose influence on Jews and Christians for the past millennium has been monumental. Indeed scholarship since the Renaissance has interpreted the book as ranging from fabula to history. In his concluding remarks, author suggest that Sefer Yosippon has in addition to its historical methodology, to its literary innovations and brilliant style unique in its time, a possible polemical response to the vicissitudes of the Jews in southern Italy during the several generations following the Byzantine persecutions in southern Italy.